Using Flexible Polyimide as a Substrate to Deposit ZnO:Ga Thin Films and Fabricate p-i-n α-Si:H Thin-Film Solar Cells - Fang-Hsing Wang; Cheng-Fu Yang; Min-Chu Liu (International Journal of Photoenergy)
The GZO thin films were deposited on the polyimide (PI) substrates to investigate their properties for the possibly flexible applications. The effects of substrate temperature (from room temperature to 200°C) on the surface and cross-session morphologies, X-ray diffraction pattern, optical transmission spectrum, carrier concentration, carrier mobility, and resistivity of the GZO thin films on PI substrates were studied. The measured results showed that the substrate temperature had large effect on the characteristics of the GZO thin films. The cross-section observations really indicated that the GZO thin films deposited at 200°C and below had different crystalline structures. The value variations in the films’ optical band gap (Eg) of the GZO thin films were evaluated from plots of  (αhν)2=c(hν-Eg), revealing that the measured Eg values increased with increasing deposition temperature. Finally, the prepared GZO thin films were also used as the transparent electrodes to fabricate the α-Si amorphous silicon thin-film solar cells on the flexible PI substrates, and the properties of which were also measured. We would also prove that substrate temperature of the GZO thin films had large effect on the characteristics of the fabricated α-Si amorphous silicon thin-film solar cells.